COMPUTING COMPLEXITY OF A NEW TYPE OF THE DIAPHONY - Dimitrievska Ristovska, Vesna; Stoilova, Stanislava; Grozdanov, Vassil; Kusakatov, Vancho (My University, 2012)
In the present paper we introduce a new version of the diaphony, the so-called weighted ( ( ); ) W b γ - diaphony. It is shown that the ( ( ); ) W b γ - diaphony is a numerical measure for uniform distribution of sequences in [0,1)s . The computing complexity ( ) 2 O N of the ( ( ); ) W b γ - diaphony of an arbitrary net, composed of N points in [0,1)s is obtained.